RELIGIOUS AND SECULAR BALANCE IN SOCIETY - Kudratova Umida; Zokirova Asaloy Azamat qizi (Web of Journals Publishing, 2025)
The article explores the significance of religious and secular balance in society. It analyzes the historical development of religious and secular values, their role in modern society, and the importance of their harmony in preventing extremism and radicalism. The example of Uzbekistan illustrates the integration of these principles.
Keywords: Religious balance, secularism, spirituality, harmony, extremism, radicalism, globalization, Uzbekistan, religious freedom.